Implementasi REST API Media Informasi Kehilangan dan Penemuan Barang Berbasis Android (Studi Kasus: Kampus 1 Universitas Teknologi Yogyakarta) - Muhammad Ifdhal Rumalutur; Farida Ardiani (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Losing an item is a condition where a person part with an item that previously existed to become non-existent. Yogyakarta Technology University students still often experience lost items around campus area 1. Students who experience loss usually use social media to spread information to each other, but this is still less effective because the information uploaded by students can be covered by the content or status uploaded. by other students. The impact that occurs when there is no information system is that the dissemination of information related to lost and found items is not on target so that it is more difficult for students to find their lost items again. The aim of this research is to design a system as a medium for information regarding the loss and discovery of goods in the Yogyakarta University of Technology campus 1 area. The method in this research uses the waterfall model. The results of this research are to produce an Android-based application that can make it easier for students to exchange information regarding lost and found items around the Yogyakarta University of Technology campus 1 area so that it is easier for students to find and return items to students who have lost items.